2022
DOI: 10.3390/ijms23052650
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Analysis of Reversibility of the Cell Death Program in Ethanol-Treated Neuronal PC12 Cells

Abstract: Neurodegenerative diseases are generally characterized clinically by the selective loss of a distinct subset of neurons and a slow progressive course. Mounting evidence in vivo indicates that large numbers of neurons pass through a long period of injury and dysfunction before the actual death of the cells. Whether these dying neurons can be rescued and return to a normal, functional state is uncertain. In the present study, we explored the reversibility of the neuronal cell death pathway at various stages by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
(69 reference statements)
2
7
1
Order By: Relevance
“…Incubating neuronal PC12 cells with SR-18292 at a concentration of 100 µM after EtOH removal for 20 h resulted in 100% cell death. This is in stark contrast with our previous findings on cell viability that more than 90% neuronal PC12 cells survived and recovered from 3 h exposure to EtOH [ 17 ]. It indicates the critical role of PGC-1α-mediated mitochondrial biogenesis in the recovery of neuronal PC12 cells from EtOH-induced cellular degeneration.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Incubating neuronal PC12 cells with SR-18292 at a concentration of 100 µM after EtOH removal for 20 h resulted in 100% cell death. This is in stark contrast with our previous findings on cell viability that more than 90% neuronal PC12 cells survived and recovered from 3 h exposure to EtOH [ 17 ]. It indicates the critical role of PGC-1α-mediated mitochondrial biogenesis in the recovery of neuronal PC12 cells from EtOH-induced cellular degeneration.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study in neuronal PC12 cells showed that, by removing the cell death stimulus EtOH, dying cells could survive and recover from diverse apoptotic events that are related to neuronal cell death, including neurite retraction, nuclear condensation, DNA damage, mitochondrial fragmentation, mitochondrial membrane potential loss, increased ROS generation and increased level of intracellular Ca 2+ [ 17 ]. In the present study, we analysed the mitochondrial ultrastructure in EtOH-treated neuronal PC12 cells and found fragmented mitochondria with swollen structure, disrupted cristae, and less electron-dense mitochondrial matrix (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic factors such as brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and ciliary neurotrophic factor (CNTF) have been demonstrated to increase neural repair and recovery, promoting neuroprotection and regeneration [ 42 ]. Our previous study in neuronal PC12 cells showed that recovery of mitochondrial impairment, including mitochondrial fragmentation and membrane potential loss, did not depend on exogenous NGF [ 17 ]. prRGCs are routinely cultured in media that contain the neurotrophic factors BDNF and CNTF.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is generally considered to be irreversible: once initiated, cells are committed to die. However, recent studies have shown that cells can reverse the process of cell death and recover to normal morphology when the cell death stimulus is removed, even at late stages of apoptosis [ 14 17 ]. Reversibility of apoptosis opens up a new, previously unexpected phenomenon in the field of regulated cell death, and may be helpful to rescue cells that are difficult to regenerate, like CNS neurons, such as RGCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation